2020
DOI: 10.1177/1557988320906980
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Masculine Norms, Depression, and Mental Health Service Utilization: Results From a Prospective Cohort Study Among Emerging Adult Men in the United States

Abstract: The purpose of this study was to examine the role of multidimensional masculine norms (“status,” “toughness,” “anti-femininity”) on depression and mental health service utilization among emerging adult men in the Northeast United States. This study examines substance use and hostility as secondary outcomes and depression status as an effect moderator on the relationship between masculine norms and mental health service utilization. This study used data from a prospective cohort study that followed 18- to 25-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 66 publications
1
28
0
3
Order By: Relevance
“…Yousaf and colleagues [38] further showed a negative correlation indicating that higher AtTMRN is associated with worse attitudes toward seeking psychological help in men but not women. Further research based on male samples showed associations between AtTMRN and psychological help-seeking intentions [39], attitudes towards seeking psychological help [40], a willingness to seek help for mental health issues [41], and a reduced frequency of mental health service visits [42].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Yousaf and colleagues [38] further showed a negative correlation indicating that higher AtTMRN is associated with worse attitudes toward seeking psychological help in men but not women. Further research based on male samples showed associations between AtTMRN and psychological help-seeking intentions [39], attitudes towards seeking psychological help [40], a willingness to seek help for mental health issues [41], and a reduced frequency of mental health service visits [42].…”
Section: Introductionmentioning
confidence: 92%
“…This line of research supports the perspective that the internalization of male role norms (e.g., the need to be self-reliant) presents one major reason hindering men to engage in psychotherapy. However, a limitation of previous studies is that only the attitude or intention to start psychotherapy was measured but not the actual psychotherapy use [40][41][42]. Additionally, most of the studies investigated college student samples and did not sufficiently include individuals with psychological distress or control for it, suggesting the limited generalizability of previous studies to the population of psychologically distressed individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional masculinity is mostly associated with negative health behaviours ( Addis & Mahalik, 2003 ; Courtenay, 2000 , 2011 ; Springer & Mouzon, 2011 ). However, emerging studies have explored the potential for the endorsement of some masculine norms to predict positive health behaviours such as increased use of mental health services and preventative self-care ( Levant et al, 2011 ; Salgado et al, 2019 ; Sileo & Kershaw, 2020 ). When exploring whether theoretical positive masculinity constructs are more broadly socially accepted and enacted, McDermott et al (2019) found some traditional masculine ideals usually captured as negative traits can to a degree be associated with socially acceptable responses or positive behaviours, such as being successful in one's job.…”
Section: Discussionmentioning
confidence: 99%
“…Participants attending interventions 1 and 2 had signi cantly lower total conformity to masculine norms, power over women, and heterosexual self-preservation than expected for this population group. Indeed, these maladaptive masculine traits are barriers to help-seeking as total conformity to masculine norms negatively in uence help-seeking attitudes [14,15,19,20], power over women contributes to worse mental health outcomes [24], and greater heterosexual self-preservation can be seen as a dimension of antifemininity contributing to greater help-seeking reluctance [21]. Additionally, winning was signi cantly higher for participants in intervention 2 which can be considered as an adaptive trait as it has been shown to encourage help-seeking and act as a protective factor from mental health di culties [25].…”
Section: Discussionmentioning
confidence: 99%